PERENCANAAN MANAJEMEN KONSTRUKSI PADA PEMBANGUNAN STRUKTUR BUNKER GEDUNG RADIOTERAPI RSUD Dr. SOEDARSO KOTA PONTIANAK: PERENCANAAN MANAJEMEN KONSTRUKSI PADA PEMBANGUNAN STRUKTUR BUNKER GEDUNG RADIOTERAPI RSUD Dr. SOEDARSO KOTA PONTIANAK - Gustianti Kurnia, Aura Febri; Abduh, M; zuraida, ida (RETENSI, 2024)
The construction of the Bunker in the Radiotherapy Building is a project built with specific requirements, particularly in its Construction Management. To achieve the intended goals, it is essential to have a good management plan to ensure that the project construction yields effective, efficient, and economical results. In the Final Project, the author focuses on five elements of construction management; Cost : which deals with the calculation of the Implementation Budget Plan. Time ; Addressing the creation of a Network Planning using the Critical Path Method and a Time Schedule. Quality: Developing a standard quality control table. Health, Safety, and Environment: Establishing the classification and control of accident risks, determining Personal Protective Equipment, and specifying Safety and Health Work Procedures. The result of this Final Project is that the author can make Cost Management Planning, namely RAP with a cost of Rp. 7,741,778,071.76-. Time Management Planning includes a Time Schedule and NWP using the CPM, resulting in a duration of 11 weeks or 79 days. For Human Resource Management Planning, a total of 108 workers are required for all work items. Quality Management Planning is based on the quality (Qc) and quantity (Qa). Occupational Health and Safety Management System planning involves identifying hazards and controlling risks. The requirement for Personal Protective Equipment and Personal Protective Work Equipment can be determined based on hazard identification and risk assessment. Keywords: Management Construction, Cost, Time, Human Resources, Quality, and Occupational Health and Safety.